A DEVELOPMENT OF INTERACTIVE E-MODULES FOR HIGH SCHOOL PHYSICS LEARNING BASED ON PROBLEM BASED LEARNING (PBL) - Arifin, Imam; Zurweni, Zurweni; Habibi, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
Interactive multimedia is one factor that can increase student interest and learning outcomes. One of the interactive multimedia is interactive e-modules. The aim of this research is to describe the planning, design and development of learning e-modules, assess the theoretical, conceptual and practical feasibility of interactive e-modules, describe peer responses and describe the attractiveness of interactive e-modules based on Problem Based Learning (PBL). The research method used is Research and Development. The research subjects were students at Ash-Shiddiiqi Jambi IT High School. The development model used as a reference is the Lee and Owen development model, with stages Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The research results showed that the material expert validation results were 97.33% with a very feasible category. And the validation results from media experts were 90.77% in the very feasible category. And the teacher response was obtained with a score of 90.91% in the very appropriate category. Then the one-to-one trial obtained a score of 77.22% in the good category. Next, a small group trial was carried out with a score of 84.73% and a field trial of 89.26%. So interactive e-modules for PBL-based physics learning are suitable for use by SMA IT Ash-Shiddiiqi Jambi students.